Actividad inhibitoria de hojas y corteza de Matisia cordata Bonpl y corteza de Cecropia strigosa Trécul sobre α - glucosidasa - Huamán Núñez, Jooy (2023)
An effective strategy to control type 2 diabetes is to hydrolytically inhibit complex polysaccharides by pancreatic ?-amylase, reducing glucose uptake through ?-glucosidase inhibition. Our objective was to determine the inhibitory activity of Matisia cordata Bonpl leaves and bark. (MCB) and Cecropia strigosa Trécul bark (CST) on ? – glucosidase, tested at concentrations of 100, 250, 500 and 1000 ?g/mL. In none of the tested concentrations, the MCB leaf extract demonstrated an inhibition greater than 50%, that is, it is not considered active on ?-glucosidase; while the bark extract at 1000 ?g/mL showed 55.08% and the CST bark obtained 50.42%. An IC50=908.04 ?g for MCB bark extract; Compared with that of CST bark with IC50= 984.94 ?g, it allows us to conclude that the MCB bark extract is the most active ?-glucosidase inhibitor.